METODE PEMICUAN DALAM UPAYA MENINGKATKAN BUDAYA PEMBERANTASAN SARANG NYAMUK (PSN) PADA MASYARAKAT - Emilia Chandra; Zunidra Zunidra; Bambang Ariyadi; Mei Ahyanti (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
The purpose of this development is to produce an educational model "Triggering PSN Mobile," while the specific objectives are to describe the development process, determine feasibility, describe the stages, and find out the effect of the educational model for eradicating mosquito nests on the knowledge, attitudes, and behavior of the community. This research method is quantitative research with a research and development (R&D) design. This research uses a one-group pretest and posttest design. The focus of this study is to test the effectiveness of the educational model with the PSN reminder application in increasing the culture of eradicating mosquito nests in the city of Jambi. The variables studied include knowledge, attitudes, and behavior. The results of this study resulted in the PSN Mobile Triggering educational model, which is a field triggering model followed by Android-based triggering, which has been declared feasible after going through the validation stages of 100% health promotion experts, 94.55% IT experts, 92% educational technology experts, and 80 practitioners. % and 93.85% one-on-one trials, 95% small group trials, and 96% large group trials. The PSN Mobile Triggering Product is effective in increasing the knowledge, attitude, and behavior of the jumantik rumah to 100% in the implementation of mosquito nest eradication. The conclusion obtained is that the educational model is feasible and effective to use to increase the knowledge, attitude, and behavior of Jumantik Rumah in carrying out the eradication of mosquito nests.